Analisis Kesulitan Siswa Melakukan Latihan Teknik Passing Long Pass dalam Permainan Sepak Bola Di SMPN 03 Ella Hilir - Dio Anuar; Kurnia Dyah Anggorowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study was to analyze in depth the difficulties experienced by ninth-grade students of SMPN 03 Ella Hilir in performing the long pass passing technique in soccer. The research method used was descriptive qualitative research involving 10 ninth-grade students who constituted the entire population of the class (total sampling). Data were collected through a long pass technique practice test using a four-aspect assessment rubric validated through expert judgment, in-depth interviews with physical education teachers and soccer coaches, and photo documentation during the test implementation. Data analysis included data reduction, data presentation, and conclusion drawing, while data validity was examined through source triangulation. The results showed that all students experienced significant difficulties in four aspects of the long pass technique, namely improper supporting foot position as the most fundamental difficulty, leg swings that were too short and ineffective, very low kicking accuracy as a cumulative effect of the previous two difficulties, and inconsistent eye focus toward the target. In conclusion, these four difficulties were interrelated and comprehensive, indicating the need for a more systematic, structured, and intensive technical training program to improve students’ mastery of the long pass passing technique. Keywords: Descriptive Qualitative, Difficulty Analysis, Long Pass Passing, Physical Education, Soccer